(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Since its inception in the late 1800s, the electrical infrastructure has only grown throughout the previous century. The demand for and need for this infrastructure will increase as the world’s reliance on electrical energy grows. This puts a burden on the present infrastructure, demanding frequent equipment improvements. With the fast adoption of electric vehicles, for example, power lines that were previously suitable for family and commercial loads will be stretched to their limits, and an upgrade may not be a possibility. In this case, microgrids, or localized generation and consumption, are a superior option. However, because to their dispersed nature, controlling and coordinating the generating sources is exceedingly challenging. To address this problem, an alternate microgrid architecture with control localized to individual sources is proposed. This is the essence of microgrid distributed control. This research describes and evaluates a micro-grid architecture that comprises many, independent sources connected by a shared DC bus, as well as built-in battery storage, power monitoring, and protection systems.